Efektivitas Konseling Kelompok Menggunakan Pendekatan REBT Untuk Mengurangi Kecemasan Siswa dan Meningkatkan Kepercayaan Siswa Kelas XII Dalam Mengikuti Ujian Masuk Perguruan Tinggi Negeri di MAN 1 Aceh Tenggara - Wulandari, Nilas Siti; F, Firman; N, Netrawati; Nazri, Mohd (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Early adulthood Class in order to be able to graduate in the desired major at a State University, which suits the student's desires and abilities, and all of this is of course not an easy thing for class XII students to pass, so this often makes students feel anxiety and also reduces the level of self-confidence in students, in facing their future. This research uses a literature study method using a qualitative approach, describing a literature review as a written synopsis of books, papers and journal articles that provide knowledge and theory. The results of this research are reducing student anxiety and increasing student confidence using the REBT approach in group counseling.